THE SKILL OF USING ETHNO-FOLKLORISM IN ISAJON SULTAN’S STORY "BIBI SALIMA" - Kurbanova Feruza Azamovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the story "Bibi Salima" by Isajon Sultan is analyzed, which is one of the famous authors of contemporary Uzbek literature and the writer’s ability to use ethno-folklorism in order to clearly reveal the character of the hero is shown. The work focuses on prayer, one of the ancient traditions of our people.